Pemahaman Hukum di Masyarakat Tentang Dampak Membuang Sampah Rumah Tangga di Wilayah Kelurahan Nyapah Kecamatan Walantaka Provinsi Banten - Hera Damayanti; Diana Romdhoningsih; Fahisatul Jannah; Mohammad Ali; Fadilah Fadilah; Nursaidah Ahmad; Saniati Saniati; Nur'asiah Nur'asiah; Fathurrohim Fathurrohim; Mafruroh Mafruroh (Jurnal Pengabdian Masyarakat Waradin, 2024)
Nyapah sub-district, which is one of the 14 sub-districts in Walantaka District, has problems faced by the community and the nyapah sub-district apparatus itself, namely not understanding and knowing about the legal regulations related to waste management, as well as handling waste that can actually provide good benefits from an environmental perspective. as well as the economy of the community in Nyapah sub-district. And there is also no Waste Bank for waste management. This service activity is important in providing legal education about waste and so that the community in Nyapah sub-district is legally aware of the importance of good and correct waste management in accordance with applicable legal regulations. The method used is descriptive with a qualitative approach by collecting data, including interviews, observation and documentation. The result of this service is that the community and Nyapah sub-district officials can know and understand the regulations regarding waste management contained in the law. No. 18 of 2008 concerning Waste Management, Government Regulation no. 27 of 2020 concerning Specific Waste, Minister of Environment and Forestry Regulation No. 14 of 2021 concerning Waste Management at Waste Banks, and Serang City Regional Regulation Number 7 of 2021 concerning Waste Management.